The link between surface water and groundwater-based drinking water – strontium isotope spatial distribution patterns and their relationships to Danish sediments. (October 2020) - Frei, Robert; Frei, Karin M.; Kristiansen, Søren Munch; Jessen, Søren; Schullehner, Jörg; Hansen, Birgitte
Abstract: The hydrological relationship between surface waters and groundwaters in many regions of the world is well known and the effects of their mutual interaction and interaction with the soils and bedrocks, with respect to resulting changes in their chemical composition, are well studied. In this study we add to this knowledge by comparing the distributional patterns of strontium (Sr) isotopes in previously published 192 surface water samples with those of newly acquainted Sr isotope data from groundwater-based drinking water samples extracted from 163 of the major waterworks in Denmark. The aim is to investigate potential compositional changes that might derive from the interaction with the aquifer lithology or overlying sediments and soils. The average Sr isotope signatures of surface and groundwater-based drinking waters define 87 Sr/ 86 Sr values of 0.7096 ± 0.0015 (2σ) and 0.7088 ± 0.0013 (2σ), respectively. The skewed distribution of Sr isotope compositions in groundwaters towards lower 87 Sr/ 86 Sr values indicates enhanced contribution of natural carbonate-derived strontium with depth, while slightly elevated 87 Sr/ 86 Sr signatures in surface waters may reflect the diminished contribution of Sr from carbonates in the glaciogenic sediments due to their progressive acid dissolution. Strontium concentrations [Sr] in groundwater-based drinking water from the participating major waterworks define a country-wide average of 1.17 mg/L and the distributional pattern shows an East – West decreasing trend. Lowest concentrations are found in the West Jutland glaciogenic province (WJGP; average [Sr] = 0.36 mg/L) and in the northernmost tip of Jutland. A corresponding pattern, although less pronounced, is also depicted by the 87 Sr/ 86 Sr signatures of groundwater-based drinking water, whereby increasing 87 Sr/ 86 Sr values from Zealand through Funen into the Jutland peninsula correspond with increasing thickness of glaciogenic overburden providing (though mass-balance wise subordinate) radiogenic Sr to the natural carbonate-dominated groundwaters. The highest 87 Sr/ 86 Sr values are recorded in waters from northern Jutland, possibly reflecting the admixture of radiogenic strontium from late glacial and post-glacial glacio-isostatic adjustment-related marine aquifers. Generally, the surprisingly rather homogeneous and similar distributional patterns of 87 Sr/ 86 Sr signatures of Danish aquifers and surface waters implies a strong and dominant control of Sr by natural clastic (reworked) carbonate components in the Quaternary, Miocene and Holocene sediments, and to lesser degree (with the exception of northern central Jutland and Eastern Zealand) from the pre-Quaternary limestone dominated " basement" directly. Our results are consistent with a tight hydrological and geochemical interrelationship between surface waters and groundwaters in Denmark. There is a need for further investigations of the effects of advanced treatment of soft (acidic) groundwater-based drinking water on the concentrations and isotopic signatures of trace elements such as Sr. However, our study lends support for the adequate use of Sr isotope signatures of either of these waters to characterize the isotope compositional range of bioavailable fractions relevant for authenticity identification, forensic studies, and for prehistoric and modern human and animal proveniencing. Graphical abstract: Image 1 Highlights: Report of Sr concentrations and isotope compositions of 163 Danish drinking waters. Patterns of 87Sr/86Sr and Sr concentrations reflect nature of sediments. Distributional patterns of groundwaters resemble those of surface waters. Sr in groundwater is a mixture of limestone and Quaternary/Tertiary sediment sources. Sr isotopes in groundwaters are suitable for provenance studies.